Global Cities as the Hubs of New Transnational Actors - N. A. Sluka (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
In the context of the world development paradigm shift and the transition to a network structure, so-called new transnational actors are beginning to play an increasing role in global governance processes, their activity is constantly growing and their composition is expanding. In the economic sphere their core is made up of transnational corporations (TNC), in the political sphere  – of international organizations of different profiles and status. Placing their headquarters in cities, such structures, together with the institutions of traditional subjects of international relations, largely determine both the set of command and control functions over urban agglomerations, their competitiveness, sustainability of development and the variability of the configuration of the General framework of “centers of power” operating on the world stage. Their influence growth in the context of desovereignization process development means the approximation of the historical transition in the spatial organization of the international community from its traditional “countries-nations” model to the “archipelago of cities”, which is a set of centers of different rank and functional profile, closely interacting on a global scale.The global cities concept, which emerged in the 1990s, is aimed at revealing this phenomenon. The explanatory part of this concept is based on the superposition of network structures of global firms highly specialized business services in global cities. The article discusses the main directions in modern research of global cities, argues for the need for a qualitative update of existing approaches, and the importance of new transnational actors in their formation. An assessment of the dynamics and localization of the headquarters of the world’s leading TNCs and international organizations is given. The revealed asymmetry in their placement refutes the hypothesis that global cities are equally attractive. Based on the rating and grouping of centers, several types of hubs of new transnational actors were identified, including complex ones headed by “hegemonic cities” (New York, London, Paris), and specialized ones of various ranks – geoeconomic and geopolitical. Given the relevance and significance of the phenomenon of new transnational actors based in urban agglomerations, it is assumed that a productive study of the features of their formation, composition, specialization, placement and interaction mechanisms can become the subject field of a new scientific problem area at the intersection of a number of disciplines  – geopolitical urbanism, which can make a significant contribution to the study of the contours of future global transformations.